2013
DOI: 10.1016/j.jacc.2013.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol Reduces Left Ventricular Mass in Patients With Type 2 Diabetes and Left Ventricular Hypertrophy

Abstract: Allopurinol causes regression of LVM in patients with T2DM and LVH. Regression of LVH has been shown previously to improve CV mortality and morbidity. Therefore, allopurinol therapy may become useful to reduce CV events in T2DM patients with LVH. (Allopurinol in Patients with Diabetes and LVH; UKCRN 8766).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 44 publications
6
102
0
3
Order By: Relevance
“…26 Allopurinol is associated with a risk of significant side effects although seems to be generally well tolerated 27 including at higher doses ≤600 mg in recent studies. 10,11,[22][23][24] UA level fell by 0.14 mmol/L in allopurinoltreated patients, with a significantly greater change with highdose treatment (0.15 compared with 0.11 mmol/L). However, this difference was small (0.038 mmol/L) and whether this small change in serum UA is the cause of the differences we found, or whether the findings are UA independent, requires thoughtful prospective study.…”
Section: Dose-dependent Responsementioning
confidence: 87%
See 1 more Smart Citation
“…26 Allopurinol is associated with a risk of significant side effects although seems to be generally well tolerated 27 including at higher doses ≤600 mg in recent studies. 10,11,[22][23][24] UA level fell by 0.14 mmol/L in allopurinoltreated patients, with a significantly greater change with highdose treatment (0.15 compared with 0.11 mmol/L). However, this difference was small (0.038 mmol/L) and whether this small change in serum UA is the cause of the differences we found, or whether the findings are UA independent, requires thoughtful prospective study.…”
Section: Dose-dependent Responsementioning
confidence: 87%
“…7 In patients with coronary artery disease, chronic kidney disease, and diabetes mellitus, allopurinol has been shown to reduce left ventricular hypertrophy. 10,22,23 This effect seems to be BP independent (although the studies may have lacked power to demonstrate a BP lowering effect per se). In patients with coronary artery disease, it has been found to improve myocardial oxygen utilization, with improved angina symptoms and exercise capacity.…”
Section: Rationale For Assessing Allopurinol Usementioning
confidence: 99%
“…In the Losartan Intervention for Endpoint Reduction (LIFE) study, Dahlof et al (7) showed that 29% of the cardio-protective effect of losartan was attributed to this drug's hypouricemic properties. A recent study (8) indicated that high-dose allopurinol can cause regression of left ventricular mass through the strict control of blood uric acid levels; therefore allopurinol may be useful for reducing cardiovascular events in T2DM patients with left ventricular hypertrophy. Several recent studies have found that asymptomatic HUA is an important risk factor for the occurrence and progression of atherosclerosis in patients with T2DM (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…At low levels, Allopurinol competitively inhibits xanthine oxidase by acting as a substrate, however, at increased levels, it acts as a non-competitive inhibitor [68]. The accidental discovery of the role of xanthine oxidase in the production of superoxide, paved the way for more research in this area for development of several other potent xanthine oxidase inhibitors of different classes and the exploration of potential anti-oxidant effect of Allopurinol [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Apart from its established use in gout and tumor lysis syndrome, the pleiotropic effects of Allopurinol is being explored in a number of conditions [67].…”
Section: The Therapeutic Potential Of Allopurinolmentioning
confidence: 99%